2020
DOI: 10.3389/fpsyg.2020.615041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Emotional Valence and Concreteness on Children’s Recognition Memory

Abstract: There are considerable gaps in our knowledge of how children develop abstract language. In this paper, we tested the Affective Embodiment Account, which proposes that emotional information is more essential for abstract than concrete conceptual development. We tested the recognition memory of 7- and 8-year-old children, as well as a group of adults, for abstract and concrete words which differed categorically in valence (negative, neutral, and positive). Word valence significantly interacted with concreteness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Finally, Kim et al (2020) tested a different cognitive process, children’s recognition memory, for the interaction of valence and concreteness. They presented 7- to 8-year-old children with spoken word stimuli that varied on both valence and concreteness.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Kim et al (2020) tested a different cognitive process, children’s recognition memory, for the interaction of valence and concreteness. They presented 7- to 8-year-old children with spoken word stimuli that varied on both valence and concreteness.…”
Section: Introductionmentioning
confidence: 99%
“…In research on language use, cutting-edge approaches investigate dialogue as a form of joint action [30,31], and new tools allow researchers to explore the interactional dynamics underlying language use [32][33][34][35]. Studies show that interaction facilitates abstract thought and problem-solving [6,36,37] and reveal that emotions [38][39][40][41][42] and social interaction [43][44][45] are paramount for abstract concept acquisition and use.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Lund et al [51] conducted a processing study with three age groups between 5 and 7 years, also finding that the middle age group (here 6year-olds) showed an effect of emotional valence that was specific to abstract concepts, but only for positive not negative valence. Finally, Kim et al [72] showed that for recognition memory in 7-8-year-old children, valence interacted with abstract concepts, but only for negative words. These acquisition studies are generally interpreted as supporting the idea of emotional grounding, although the fact that only partial effects were obtained (i.e.…”
Section: (A) Evidence For Emotional Groundingmentioning
confidence: 99%
“…[17] and Kim et al . [72] offer plausible post hoc explanations why the children in the respective studies showed only partial effects. However, in the case of Ponari et al [17], it was positive valence that stood out; in the case of Kim et al .…”
mentioning
confidence: 99%